Modeling the lateral behavior of freeze-thaw damaged reinforced concrete columns including reinforcement slip and shear effects. (15th June 2021) - Zhang, Yixin; Zheng, Shansuo; Li, Lei; Dong, Liguo; Ji, Jinming; Ruan, Sheng
Highlights: A computationally efficient model is developed for freeze-thawed RC columns. A new analytical solution is proposed for calculating reinforcement slip. The freeze-thaw damage on column shear behavior is considered. The proposed model is validated by comparing actual and simulated cyclic curves. Abstract: This paper focuses on modeling the lateral load-deformation response of reinforced concrete columns subjected to freeze-thaw cycles (FTCs). Freeze-thaw effects are accounted for by means of a non-uniform reduction in concrete strength and bond deterioration between the steel and concrete. The new column response model that is proposed includes deformations due to flexure, reinforcement slip, and shear effects, and the influence of freeze-thaw effects on each of these aspects. The slip displacement is formulated and solved using governing equations among four bond fields. The moment-rotation relationship is then developed and introduced into the zero-length spring element to compromise the rotations caused by reinforcement anchorage slip and by curvatures over the column height. A shear spring element is used in series to represent the shear backbone curve and to capture the onset of shear failure. The proposed model is validated using experimental data on freeze-thaw damaged columns with a wide range of typical design parameters. Overall, the proposed column model accurately simulates the cyclic behavior of both flexure and flexure-shear columns that experience freeze-thaw cycles.